ANALISIS KESALAHAN PENGGUNAAN HURUF KAPITAL PADA KARANGAN DESKRIPSI SISWA UPTD SDN 1 SLEMAN LOR PADA PEMBELAJARAN JARAK JAUH - Rahayu, Era; Sundari, Nenden; Suzanti, Lizza (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This research is based on something that is often overlooked in learning, one of which is when writing an essay, which is not paying close attention to the use of capital letters. This research aims to understand the use of capital letters in students' descriptive essays and to find appropriate teaching materials to anticipate errors in the use of capital letters. The approach used in this study is synchronous, for the research method the researcher uses the method of language error analysis which in collecting data the researcher uses a technique, namely document analysis techniques. Researchers found 5 bad uses of capital letters, namely capital letters are used as an escort for the first letter at the beginning of a sentence, capital letters are the first letters in an element of a human name, one of which is nicknames, this capital letter is used as the first letter of the names of months, years, and days. Holidays and other major holidays, capital letters are used for the first letter of geographic names, capital letters are used as the first letters in an historical name event. From the results of an analysis of student descriptions, it was found that 21 errors in the use of capital letters were found, one of which was 9 in the use of capital letters as the main letter at the beginning of the sentence, 6 errors in the use of capital letters as the main letter of the elements of naming people including designations, 2 errors in the use of capital letters used as the main letter of the name of the month, day, year, big day or holiday, 3 errors in the use of capital letters used for the first letter of geographic naming, 1 error in the use of this letter is used as the main letter of the event and naming elements in history. Furthermore, a material in learning is made, namely giving LKS to students, namely showing a description essay that does not use capital letters very well.